The Financial Times guide to investment trusts : unlocking the City's best kept secret - Baron, John, 1959- (Financial times guides., 2020)
John Baron is a columnist, author and the founder of the investment trust website. He is best known to readers of the FT's Investors Chronicle for having successfully managed two real investment trust portfolios since 2009 - as measured by their respective MSCI PIMFA benchmarks. His popular monthly column is closely followed and helps investors - private and professional - with their investments. John has used investment trusts for over 35 years. After university and the Army, in a career spanning 14 years, he ran a broad range of charity and private client portfolios as a director of both Henderson Private Clients and then Rothschild Asset Management (RAM).